Quality of Digital Public Services in Pelabuhan Village, Samarinda, Indonesia - Hafidzatul Amanah; Sry Reski Mulka (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the quality of digital public services using the SAMAGOV application in the Pelabuhan sub-district of Samarinda City. The digitization of public services is part of local government efforts to improve the effectiveness, efficiency, transparency, and accountability of services to the community in line with developments in information technology and the implementation of the Smart City concept. This study uses a qualitative descriptive approach, with data collected through semi-structured interviews, field observations, and document analysis. Research informants include the Village Head, Village Secretary, village officials/staff, and the community as users of digital public services. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, using four dimensions of digital public service quality as the analytical framework: usability, reliability, responsiveness, and citizen support. The results showed that the SAMAGOV application improved the accessibility and efficiency of administrative services at the village level, especially for people with adequate digital literacy. However, obstacles persisted among the elderly and users with limited technological capabilities, who required assistance from village officials. In terms of reliability, digital services still face technical disruptions affected by the stability of servers and networks managed at the city level. However, the village administration has demonstrated a high level of responsiveness and support through direct assistance and the provision of digital services. Overall, the quality of digital public services through the SAMAGOV application in Pelabuhan Village is quite good, but still requires continuous improvement, particularly in strengthening technological infrastructure, increasing human resource capacity, and expanding digital literacy and awareness among the community.